THE DIFFERENCES BETWEEN ARSIPARIS AND INDEPENDENT PROFESSIONAL RECORD MANAGER - Lawanda, Ike (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2018)
In this article the author argues that the globalization and independent professionalization makes it imperative that archivists and arsiparis are engaged in a joint enterprise hence differ in the status of independence and the relationship within the government institution. This paper presents Participatory Action Research (PAR) which is an approach to research in communities that emphasizes participation and action. It seeks to understand the world by trying to change it, collaboratively and following reflection. Informants of seven record managers in Indonesia are the source of data on this research. In developing this argument, the common roots of archivist and arsiparis are examined its emergence of archives in Indonesia in the 1950s and their subsequent divergence over the next three decades. The author identifies the common ground that archivist and arsiparis share in dealing with recorded information. This common ground, which includes records integrity, archive provenance, and archive original order over time, is linked into a single unifying theme by the importance of the contextual relations. Arsiparis, record manager, and archivist are considered as two ways of managing document in organization under the same roof of governing government. The article concludes with a call for archivists and arsiparis to participate in the design of independence professionals, in order to ensure that archivists and arsiparis are acceptance within the competition of global market under the protection of independence professional association, and legitimized by the regulation of government under the constitution.